2014
DOI: 10.1039/c4ra07842j
|View full text |Cite
|
Sign up to set email alerts
|

Flexible superhydrophobic paper with a large and stable floating capacity

Abstract: Recently, one interesting wetting phenomenon was found whereby a live frog can stably stand or easily jump on a floating lotus surface. Inspired by the floating leaf, constructing a lotus-like substrate is important to provide powerful aquatic support. In this article, a flexible and light-weight superhydrophobic paper was successfully fabricated by coating a mixture of polystyrene-poly(methyl methacrylate) copolymer (PS-co-PMMA) and silica nano-particles. The micro/nano structures from the composite coating r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Color super hydrophobic paper was obtained by precipitating cellulose and color stearate on swollen cotton, and the hydrophobic paper still maintained good hydrophobic stability after abrasion. Zhang et al 20 reported a preparation method of superhydrophobic paper. By coating the mixture of silica nanoparticles and polystyrene-polymethyl methacrylate copolymer (PS-co-PMMA), flexible lightweight superhydrophobic paper with strong hydrophobicity was successfully prepared with excellent hydrophobic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Color super hydrophobic paper was obtained by precipitating cellulose and color stearate on swollen cotton, and the hydrophobic paper still maintained good hydrophobic stability after abrasion. Zhang et al 20 reported a preparation method of superhydrophobic paper. By coating the mixture of silica nanoparticles and polystyrene-polymethyl methacrylate copolymer (PS-co-PMMA), flexible lightweight superhydrophobic paper with strong hydrophobicity was successfully prepared with excellent hydrophobic performance.…”
Section: Introductionmentioning
confidence: 99%
“…To addressing these challenges, Zhang et al prepared a light‐weight, flexible and superhydrophobic cellulosic paper by simply coating the mixture of polystyrene‐poly (methylmethacrylate) copolymer (PS‐co‐PMMA) and silica nano‐particles 42 . Moreover, a superhydrophobic cellulose‐based paperboard with a WCA larger than 160°was fabricated by depositing with titanium dioxide nanoparticles using a thermal spray method 43 .…”
Section: Introductionmentioning
confidence: 99%
“…Both of nano‐ and micro‐hierarchical surface roughness and low surface energy are recognized as strong heuristic to accomplish superhydrophobic property, which is a key role to produce waterproof fabrics. Nonetheless, low surface energy modifiers are commonly fluorine‐based materials which are highly toxic and expensive, which led to limiting its wider applications …”
Section: Introductionmentioning
confidence: 99%